A Pelaksanaan Kelas Ibu Hamil Di Desa Kedungoleng Kecamatan Paguyangan Kabupaten Brebes - Endang Susilowati; Himatul Khoeroh (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
Pregnant women class is a study group for pregnant women through education or health education with a gestational age of 4 weeks to 36 weeks. The purpose of the class for pregnant women is to increase knowledge, change attitudes and behavior of mothers to understand pregnancy, body changes and complaints during pregnancy, pregnancy care, childbirth, postpartum care, postpartum family planning and newborn care. The class for pregnant women is given at least 3 times during pregnancy, a maximum of 10 people per class, husband or family participates at least 1 meeting. The method used is one day one service, namely with one meeting for class services for pregnant women with a total of 3 meetings during pregnancy. The steps taken include screening pregnant women first. The next stage is the implementation of the first meeting the facilitator delivers material about discomfort and changes that occur in pregnant women, healthy lifestyles and balanced nutrition and danger signs. The second meeting was about the danger signs of childbirth, preparation for delivery and signs of delivery, while the third meeting was about caring for newborns, postpartum mother care and post-partum family planning and ended with role play exercises for pregnancy. The results of the class activity for pregnant women, 90% of pregnant women are willing to take part in the activity and understand the materials that have been delivered by the facilitator, it is only recommended to participate in the husband or family so that they are more prepared to participate in maintaining health together.